The Effectiveness of Using Lectora Based on Aceh Culture on Linear Equation System Material - Fadilah Fadilah; Rizki Amalia; Roni Priyanda (Budapest International Research and Critics University, 2020)
The aim of this study to analyze the effectiveness of using Lectora based on Aceh culture on Linear Equation System Material. This research uses a quantitative descriptive research approach. The research design used was the One Group Pretest-Posttest Design. The conclusions of this study are as follows: 1) the results of the observation of the teacher's ability in managing learning were 83.92% with good categories; 2) the results of observations of student activities during the learning process were quite active with a percentage of 73.08%; 3) The results of the percentage of student response questionnaires were 51.67%, which means that most students responded well to the use of Aceh culture-based lectora media on the material of linear equation systems; 4) Statistical test with t test obtained t count = 30,11865 and t table = 1,729133 ( = 0,05), t count > t table means that the use of media is effectively used; and 5) Aceh Culture-Based Lectora Media is effectively used in learning linear equation systems. The results of the overall data analysis indicate that the use of Aceh Culture-Based Lectora is effective for student learning outcomes on linear equation material.